Bioactivities and Health Benefits of Mushrooms Mainly from China - Jiao-Jiao Zhang; Ya Li; Tong Zhou; Dong-Ping Xu; Pei Zhang; Sha Li; Hua-Bin Li (Molecules, 2016)
Many mushrooms have been used as foods and medicines for a long time. Mushrooms contain polyphenols, polysaccharides, vitamins and minerals. Studies show that mushrooms possess various bioactivities, such as antioxidant, anti-inflammatory, anticancer, immunomodulatory, antimicrobial, hepatoprotective, and antidiabetic properties, therefore, mushrooms have attracted increasing attention in recent years, and could be developed into functional food or medicines for prevention and treatment of several chronic diseases, such as cancer, cardiovascular diseases, diabetes mellitus and neurodegenerative diseases. The present review summarizes the bioactivities and health benefits of mushrooms, and could be useful for full utilization of mushrooms.